Empowering The Papring Community Through The Jemparing Wangi Program Towards Social Transformation - Muhammad Reza Hudaya; Galis, Nandya Erlisa; Fahmi, Muhammad Naufal Aditya; Hutama, Andy Yudha; Sudarsono, Gatot; Dewi, Titis Puspita (Prospect Publishing, 2022)
Community empowerment is carried out to facilitate vulnerable communities to gain access to resources. Community empowerment efforts can be carried out by the government, companies, or from the community itself. Access to capacity building, infrastructure, and regular assistance can encourage community independence. However, community empowerment efforts are not necessarily able to make the community independent. This study aims to see the best practice of community empowerment in the Jemparing Wangi Program by PT Pertamina Patra Niaga Integrated Terminal Tanjung Wangi in Papring. This study uses qualitative methods with data collection techniques in the form of participant observation, in-depth interviews, and documentation. The results of the study explain that community empowerment activities by PT Pertamina Patra Niaga Integrated Terminal Tanjung Wangi in Papring are able to encourage independent communities. This is shown by the independence of the community through the ability of community groups to manage natural resources in their area in a sustainable manner.